Worldwide development of agronomic management practices for quinoa cultivation: a systematic review - Taaime, Nawal; Rafik, Sifeddine; El Mejahed, Khalil; Oukarroum, Abdallah; Choukr-Allah, Redouane; Bouabid, Rachid; El Gharous, Mohamed (Frontiers in Agronomy, 2023)
Quinoa (Chenopodium quinoa Wild.) is a drought and salinity-tolerant crop that originated in the Andes over 7000 years ago. It is adapted to different agroecological areas and can be grown from sea level to an altitude of 4000 m. The outstanding nutritional status of quinoa, with its high content of proteins, vitamins, and minerals, makes it a promising crop able to combat hunger and malnutrition in different countries in the 21st century. Quinoa cultivation has expanded from South America to Africa, Europe, Asia, and North America. Reviewing quinoa cropping practices will provide farmers with adequate recommendations for improving the agronomic and environmental sustainability of quinoa cultivation worldwide. For this reason, we conducted a systematic review of agronomic management practices in 148 field experiments conducted worldwide from 2000 to 2022. The collected data from the literature were analyzed and presented by location to determine high-performing genotypes, optimal planting dates, and other adequate cropping practices affecting quinoa performance and yield. Results showed that quinoa could be successfully cultivated in the new farming areas. Quinoa yields were higher than those reported in its place of origin, ranging from 108 kg ha-1, obtained by KU-2 in Washington State, to 9667 kg ha-1, obtained by Longli in China. Although quinoa is considered a crop with low input requirements, positive grain yield response was observed following increasing fertilization rates. Quinoa needs 2 to 4.6 kg of nitrogen to produce 1q of grain yield. In terms of phosphorus and potassium, quinoa needs 3.7 kg P2O5 and 4.3 kg K2O to produce 1 ton of total biomass. Quinoa has low water requirements (300-400 mm). However, a positive response was recorded with water quantities up to 866 mm. During our investigation, weed control in quinoa crop is still undeveloped and usually done manually. Research addressing this issue can increase quinoa yields and decrease the production cost. Our results constitute the first recommendation base for the adequate worldwide agronomic practices of quinoa crop.